My working :

$\displaystyle y(x+b) = x-a$

$\displaystyle yx + yb = x-a$

$\displaystyle yx - x = -a - yb$

$\displaystyle x(y-1) = -a - yb$

Answer $\displaystyle x = (-a - yb)/(y-1)$

Do I need to further simplify?

Thanks for the help

Printable View

- Sep 19th 2011, 03:00 AMFailInMathsGiven that y = (x-a)/(x+b), express in terms of a, b and y
My working :

$\displaystyle y(x+b) = x-a$

$\displaystyle yx + yb = x-a$

$\displaystyle yx - x = -a - yb$

$\displaystyle x(y-1) = -a - yb$

Answer $\displaystyle x = (-a - yb)/(y-1)$

Do I need to further simplify?

Thanks for the help - Sep 19th 2011, 04:15 AMFernandoRevillaRe: Given that y = (x-a)/(x+b), express in terms of a, b and y
- Sep 19th 2011, 04:23 AMFailInMathsRe: Given that y = (x-a)/(x+b), express in terms of a, b and y
- Sep 19th 2011, 04:24 AMFernandoRevillaRe: Given that y = (x-a)/(x+b), express in terms of a, b and y
- Sep 19th 2011, 04:43 AMFailInMathsRe: Given that y = (x-a)/(x+b), express in terms of a, b and y